French Principals in Secondary Education: Towards New Roles and Responsibilities? - Romuald Normand (LED Edizioni Universitarie, 2015)
The field of research on school leadership is not really developed in France. Professional literature dominates over research papers and the concept of management is not very popular among educators and academics. It is considered as connoted to business and to the market and opposed to the values of public services. French principals view themselves as «administrators» or «representatives of the State» and they are very concerned to apply national legislation and ministry's directives. Even if this notion is implicitly present within official instructions that define principals as «pedagogical and educative pilots» of schools, these executives lack real legitimacy to act on the teaching and learning issues which remain in the hands of State inspectors. So, leadership is recognized not as an official function, but rather through an implicit and blurred sense of professionalism expressed sometimes by professionals as «personal charisma», «sense of dialogue», «proximity». «Authority» and «responsibility» are the main social representations allowing principals to define their «missions» as public servants.